The People Behind the Publications: Reflections on a Decade of Reviews (Teaching and Learning Inquiry, 2022)
This article reflects on my personal experience as a TLI reviewer. It draws upon a decade of learning with and from colleagues, and connects the lessons learned from being both a reviewer and producer of SoTL output. I signpost the challenges and opportunities that belie the role of a TLI reviewer and celebrate the success the role brings. Through the role of TLI reviewer, I have learned how to reshape feedback and structure guidance to support the submissions of manuscripts to TLI.